Digital Technologies For Environmental Education And Civic Engagement: A Case Study On A Pre-Secondary Pathway For Unaccompanied Foreign Minors Preparing For Entry Into High School - Salerno, Vincenzo (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The dual transition—ecological and digital—requires a profound cultural shift. It's not about modifying individual behaviors, but promoting collective change. In a growing interethnic landscape, intercultural education plays a strategic role in civic education and global ecological and technological skills. From this perspective, educational settings that welcome unaccompanied foreign minors may be relevant, although they have remained understudied. The aim of the research, conducted with educators at a reception center for UFM in Italy, is to identify best practices for overcoming disadvantage and promoting the inclusion of UFM in secondary schools through multilingual digital classroom-labs and experiential learning workshops, such as those on horticulture and ecological and civic education. The educational community is configured as a micro-laboratory of the dual transition, where sustainability and digital innovation intertwine to build intercultural citizenship.